Cystic Dysplasia of the Rete Testis: Case Report and Systematic Review of the Literature - Contini, Giorgia; Frediani, Simone; Pardi, Valerio; Diomedi-Camassei, Francesca; Inserra, Alessandro (Frontiers in Pediatrics, 2022)
Cystic dysplasia of the rete testis (CDRT) is a rare cause of a testicular mass in children. The pathogenesis of this malformation is not clear. It is often associated with other genitourinary anomalies, commonly presenting with agenesis or dysplasia of the ipsilateral kidney. We report a case of a 9-year-old with a testicular lesion and ipsilateral renal agenesis with a diagnosis of CDRT after the histological examination. We also performed a systematic review of the literature to better understand this pathology and to choose the correct treatment and follow-up for these patients.